ICOS and Bcl6-dependent pathways maintain a CD4 T cell population with memory-like properties during tuberculosis - Moguche, Albanus O.; Shafiani, Shahin; Clemons, Corey; Larson, Ryan P.; Dinh, Crystal; Higdon, Lauren E.; Cambier, C.J.; Sissons, James R.; Gallegos, Alena M.; Fink, Pamela J.; Urdahl, Kevin B. (The Journal of experimental medicine, 2015)
Immune control of persistent infection with Mycobacterium tuberculosis (Mtb) requires a sustained pathogen-specific CD4 T cell response; however, the molecular pathways governing the generation and maintenance of Mtb protective CD4 T cells are poorly understood. Using MHCII tetramers, we show that Mtb-specific CD4 T cells are subject to ongoing antigenic stimulation. Despite this chronic stimulation, a subset of PD-1+ cells is maintained within the lung parenchyma during tuberculosis (TB). When transferred into uninfected animals, these cells persist, mount a robust recall response, and provide superior protection to Mtb rechallenge when compared to terminally differentiated Th1 cells that reside preferentially in the lung-associated vasculature. The PD-1+ cells share features with memory CD4 T cells in that their generation and maintenance requires intrinsic Bcl6 and intrinsic ICOS expression. Thus, the molecular pathways required to maintain Mtb-specific CD4 T cells during ongoing infection are similar to those that maintain memory CD4 T cells in scenarios of antigen deprivation. These results suggest that vaccination strategies targeting the ICOS and Bcl6 pathways in CD4 T cells may provide new avenues to prevent TB.